Application of an unsteady three‐dimensional computational fluid dynamics model to predictive habitat modelling of macroinvertebrates—A case study at the Ziller River in Austria. (27th July 2022) - Farhadi, Alireza; Leitner, Patrick; Graf, Wolfram; Hauer, Christoph
Abstract: The Ziller River, a tributary to the Inn in Tyrol, Austria, is affected by hydropower generation. Macroinvertebrate habitat‐preferences were investigated in the field and corresponding habitat suitability curves were applied successfully to a novel integrative assessment method based on hydrodynamic modelling. Here, a reach of the Ziller River is simulated using a three‐dimensional unsteady hydrodynamic model. The three‐dimensional simulation results are applied to a predictive macroinvertebrate habitat model. Habitat suitably indices (HSI) are calculated based on temporal alterations of bed shear stress values. Model results are free from two‐dimensional flow‐averaging approximations and demonstrate the critical information lost in lower‐order models due to simplification procedures. Shear stress values, three‐dimensional simulated velocity components, and temporal alterations of flow are provided in the current study. Considering the simulation results, the implementation of the provided supplementary simulation details in macroinvertebrate studies and the integration into further habitat investigations is discussed.